What can accelerate technological convergence of hydrogen energy: a regional perspective - Lee, Won Sang (Frontiers in Energy Research, 2023)
Focusing on technological innovation and convergence is crucial for the utilization of hydrogen energy, one of the emerging infrastructure areas. This paper analyzes the extent of technological capabilities in a region that could accelerate the occurrence of technological convergence in the fields related to hydrogen energy by using triadic patents, their citation information, and their regional information. The results of the Bayesian spatial model indicate that the active exchange of diverse but original technologies could facilitate technological convergence in a region. On the other hand, the radical technology is difficult to bring the convergence in terms of region. The findings could shed light on the establishment of R&D strategy for hydrogen technologies. This study could contribute to the dissemination and utilization of hydrogen technologies for the sustainable development of industries.